Pengaruh Rasio Beban Klaim dan Hasil Investasi terhadap Kinerja Keuangan Perusahaan Asuransi yang terdaftar di BEI Periode 2022-2024 - Anggun Fitria Novianti; Fadila Siti Nuraeni; Djalaludin Akbar; Mutiara Hayandani; Alfiana Alfiana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of the claim expense ratio and investment returns on the financial performance of insurance companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Financial performance is measured using Return on Assets (ROA) as an indicator of company profitability. This study employs a quantitative approach with an explanatory method and utilizes secondary data obtained from companies’ annual financial reports. The study uses census sampling, in which all insurance companies listed on the IDX during the 2022–2024 period are included as the research sample. The dataset consists of 18 insurance companies observed over three years, resulting in 54 panel data observations. Data analysis is conducted using panel data regression after classical assumption tests, processed with EViews 12 software. The results indicate that the claim expense ratio has no significant effect on financial performance, while investment returns have a positive and significant effect on the financial performance of insurance companies